Synthesis and Characterization of HPMpFBP Using Raman Spectroscopy, Nuclear Magnetic Resonance (NMR) Spectroscopy, and FTIR - Yusri, Wilda Triputri; Yulkifli, Yulkifli; Alizar, Alizar; Md Isa, Illyas (Jurnal Ilmu Fisika, 2021)
Synthesis is one of the models for the formation of a new drug or compound with the aim of obtaining better activity at an economical price. HPMpFBP has been synthesized by mixing of 1-phenyl-3-methyl-5-pyrazolone and 4-fluorobenzoyl chloride. In the synthesis of HPMpFBP, a new compound namely 1-phenyl-3-methyl-4-(4-fluorobenzoyl)-5-pyrozolone has been obtained. The sample then characterized by non-invasive methods using Raman spectroscopy, Nuclear Magnetic Resonance (NMR) Spectroscopy and FTIR. Through this characterization process, wavelength information, chemical shift, and functional groups (chemical structure) of HPMpFBP samples were obtained. HPMpFBP has a chemical structure of C17H13N2O2F, the highest wavelength carried out by characterization using Raman is 1643.91 cm-1, the highest chemical shift characterized by using NMR (Nuclear Magnetic Resonance) is 7.8628 ppm, and the functional groups identified by using FTIR are (O-H, C-H, C=C, C=O, C-N). Information from the HPMpFBP sample characterization process using mentioned characterization methods was compared with previously reported results.